Quality of reporting of pre-recorded music interventions in surgical patients ‐ A systematic review - Thomas L.A. Dirven; Roos Geensen; Florine Bax; Jorrit G. Verhoeven; Johannes Jeekel; Markus Klimek (Complementary Therapies in Medicine)
Background: Perioperative music interventions are promising, with substantial beneficial effects on patients. However, adequate reporting is crucial for interpreting the outcomes and implementing the interventions. Our objective is to analyze the reporting quality of perioperative music interventions and to provide recommendations and a research agenda for future trials. Material and methods: This study utilized data from a systematic review, that was conducted as part of a separate previous analysis by Geensen, Dirven et al. For this analysis, a PROSPERO registration (CRD42023427138) was formalized. The Template for intervention Description and Replication (TiDieR) checklist was adapted and used. Nineteen intervention items were assessed, categorized in the aim, the core and the implementation. Results: Due to narrowed inclusion criteria, ten music intervention studies were included. None of the studies completely reported all intervention items. The reporting of core intervention items were poorly described. Complete description of implementation items, such as fidelity and modifications, was scarce. Conclusions: Perioperative music studies often lack the complete reporting of essential intervention items. This hinders replicability, generalization of the results and might contribute to research waste. We recommend adequate reporting in future studies to avoid these problems, by using our adapted TIDieR checklist.